Design and Mechanical Evaluation of 3D-Printed Hybrid Transtibial Prosthetic Sockets Using Finite Element Analysis - Singh, Vaishnavi; Das, Rajesh; Nayak, Smita (Poltekkes Kemenkes Jakarta I, 2025)
Background: A prosthetic socket serves as a vital interface between a patient’s residual limb and the prosthetic device, playing a key role in enhancing quality of life during prosthetic rehabilitation. The design and material composition of the socket significantly influence patient comfort, safety, and long-term functionality. Aims: This study introduces a novel transtibial prosthetic socket design concept utilizing additive manufacturing techniques with two materials: Polyamide 12 (PA12) for structural integrity and Thermoplastic Polyurethane (TPU) for inner comfort, aiming to improve biomechanical performance and user comfort. Methods: The socket design integrates both PA12, recognized for its ISO-compliant safety in socket fabrication, and TPU, chosen for its flexibility and skin-friendliness. Additive manufacturing methods, including Fused Deposition Modelling (FDM) and Selective Laser Sintering (SLS), were employed in fabrication. Biomechanical validation was conducted using the Radcliffe principle for stump-socket force analysis. Additionally, bio-based modelling and mathematical simulations were utilized to optimize the socket design, including surface pressure mapping on the residual limb. Results: The dual-material socket demonstrated potential improvements in mechanical strength and patient comfort. Surface pressure mapping allowed for precise evaluation of load distribution, confirming the design’s effectiveness in reducing peak pressure points and improving fit. Conclusion: Digital fabrication technologies, particularly additive manufacturing, offer promising avenues for customized, biomechanically sound prosthetic socket design. The integration of PA12 and TPU enhances both safety and comfort, suggesting a valuable direction for future prosthetic development and theoretical research in digital health technologies.